The Regulation of Legal Responsibility: Illegal Logging Perpetrators in Indonesia and Nigeria - Suwari Akhmaddhian; Ugo Chuks Okolie; Sarip Hidayat; Yani Andriyani; Intan Tiaranita (Universitas Kuningan, 2023)
The study aims to analyze the offenders of illegal logging in Indonesia and Nigeria from its legal liability regulations. The study employed an socio-legal approach involving literary analyses on legal materials usedâ”€the statutory regulations, scientific journals and other pertinent documents. The results shows that legal responsibility for illegal logging perpetratorsÂ in Indonesia are under the Law on Forestry, the Law on Prevention and Eradication of Forest Destruction, and the Law on Cipta Kerja. In Nigeria, it is governed by several states, such as the Edo State Forestry (Amendment) Law 2002; Cross River State Forestry Commission Law 2010; and Taraba State Forestry Law 2010. Finally, the legal responsibility for illegal logging has been established in both countries. Â Accordingly, the indonesian government is suggested to disseminate the latest laws and regulations, so that the public and corporations are aware of them. Meanwhile, Nigerian government is expected to immediately issue nationwide legislation on illegal logging, so that law enforcement is not relied solely on the requirements of each state